1997
DOI: 10.1080/026404197367092
|View full text |Cite
|
Sign up to set email alerts
|

The effect of exercise on cognitive performance in soccer-specific tests

Abstract: Two experiments were carried out to examine the effect of moderate and maximal exercise on the cognitive performance of experienced soccer players. Experiment 1 examined the speed and visual search in familiar (game) and unfamiliar (non-game) contexts. Participants had to detect, as quickly as possible, the presence or absence of a ball in tachistoscopically presented slides. Participants were tested at rest and while exercising at 70 and 100% maximum power output. A main effect of exercise intensity was demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
122
3
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(131 citation statements)
references
References 14 publications
5
122
3
1
Order By: Relevance
“…This was hypothesised to be the result of heightened event specific arousal. It should be acknowledged that these findings differ to other studies that have suggested that cognitive function is impaired under conditions of physical stress (McMorris & Keen, 1994;McMorris & Graydon, 2000), but these studies have used recreational as opposed to highly trained athletes. Given that, even at the international level, basketball officials tend to be significantly older than the players, it would seem plausible that they may possess inferior physical capacities and that accumulated fatigue could influence their ability to effectively monitor on-court activities and make complex cognitively demanding decisions.…”
Section: Introductioncontrasting
confidence: 91%
“…This was hypothesised to be the result of heightened event specific arousal. It should be acknowledged that these findings differ to other studies that have suggested that cognitive function is impaired under conditions of physical stress (McMorris & Keen, 1994;McMorris & Graydon, 2000), but these studies have used recreational as opposed to highly trained athletes. Given that, even at the international level, basketball officials tend to be significantly older than the players, it would seem plausible that they may possess inferior physical capacities and that accumulated fatigue could influence their ability to effectively monitor on-court activities and make complex cognitively demanding decisions.…”
Section: Introductioncontrasting
confidence: 91%
“…Similarly, physical exercises are also known for their positive impact on performance. For example, McMorris and Graydon (1997) found that exercise could significantly increase the speed of visual search, speed of decision-making and accuracy of decision-making. Physical exercises are also known to have an impact on moods.…”
Section: Studymentioning
confidence: 99%
“…Initial accounts of exercise and arousal predicted an inverted U-shaped relationship (McMorris & Graydon, 2000;see also Yerkes & Dodson, 1908) such that moderate levels of exercise increased arousal and facilitated cognition, but when arousal approaches maximal levels performance begins to deteriorate (Levitt & Gutin, 1971;Brisswalter, Durand, Delignieres & Legros, 1995). Prior adult studies examining the effect of exercise induced fatigue on cognitive variables have evidenced an inverted U effect of increasing exercise intensity on coincidence anticipation (Lyons, Al-Nakeeb & Nevill, 2008) and reaction times (Chmura, Nazar & Kaciuba-Uscilko, 1994).…”
Section: Introductionmentioning
confidence: 99%